2000
DOI: 10.1097/00006223-200003000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Student Portfolios to Evaluate Undergraduate Nursing Programs

Abstract: A growing trend in nursing education is the use of student portfolios for program evaluation. Incorporating portfolio analysis into a school's evaluation plan requires that faculty consider how the benefits and limitations of the portfolio development process impact the entire curriculum. The primary benefit of portfolio evaluation is that it permits the correlation of competencies attained by graduates with curricular outcomes. However, portfolio development also promotes increased student responsibility for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 8 publications
2
35
0
Order By: Relevance
“…2,4,25,28,[30][31][32][33][34] Crandall suggested that in addition to providing valuable formative assessment and discussion, meeting with students on a regular basis helped to prevent the reflective portfolios from becoming a ''last ditch effort'' at the conclusion of the semester. 25 The reflective portfolio can also serve as a platform for discussion between students and faculty members to help to bridge the theory-practice gap.…”
Section: Student-faculty Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,25,28,[30][31][32][33][34] Crandall suggested that in addition to providing valuable formative assessment and discussion, meeting with students on a regular basis helped to prevent the reflective portfolios from becoming a ''last ditch effort'' at the conclusion of the semester. 25 The reflective portfolio can also serve as a platform for discussion between students and faculty members to help to bridge the theory-practice gap.…”
Section: Student-faculty Linkmentioning
confidence: 99%
“…32,37,39,[41][42][43][44][46][47][48] While not sufficient, reliability is necessary for validity; thus, low reliability in assessment methods for reflective portfolios is a serious limitation or disadvantage to their use. 49 Issues central to the debate over the extent to which reflective portfolios can be assessed reliably include the purpose of the assessment (eg, formative versus summative assessment), holistic versus component grading or assessment, rater training, and the development of the grading rubric.…”
Section: Reliability and Validity Considerationsmentioning
confidence: 99%
“…A portfolio is a document that provides a current record of all career aspects and anticipated development. Usually, a profile has a narrower focus and is constructed to meet certain requirements for example, the Nursing and Midwifery Council (2004) This definition reflects that a portfolio is much more than a document that only provides evidence that has gone before (Price, 1994), but is rather a dynamic tool that represents an individual's learning, progress and achievement over time (Wenzel et al, 1998;Karlowicz, 2000).…”
Section: Portfolio Developmentmentioning
confidence: 99%
“…A portfolio may include logbook entries, case descriptions, SOAP notes, research projects, presentation handouts, commentaries on research articles or books, and written evaluations from preceptors. 37,[42][43][44] A portfolio should contain all documents relevant to the period of training and should be used to provide periodic feedback to the learner. For example, a portfolio containing all of the documents related to a student's APEs could be used by the professional experience program director or an advisor to track student performance as well as guide the selection of future learning experiences (eg, electives).…”
Section: Portfolios To Track Student Performance/document Educationalmentioning
confidence: 99%